Our experience in optical correction of radial keratotomy consequences by scleral lenses. Clinical cases - A. V. Myagkov; N. V. Ignatova (Российский офтальмологический журнал, 2018)
Сlinical cases of rigid gas permeable lenses prescribed to the patients after radial keratotomy in the remote period are presented. The efficacy of optical correction of induced ametropias by scleral lenses is shown. Comfort sensation and high visual acuity make scleral lenses the main optical correction method for patients with irregular corneas // Russian ophthalmological journal. 2017; 10 (2): 92-6. (in Russian). doi: 10.21516/2072-0076-2017-10-2-92-96.